Locating Leadership: The Blind Spot in Alberta’s Technology Policy Discourse - Brooks, Charmaine (Education Policy Analysis Archives, 2011)
Over the last 20 years, technology and education policy discourse in Alberta, Canada has been philosophically polarized and dominated by value-neutral ways of thinking about technology (Brooks, 2011). While technology policy implementation has significant ramifications for schools and systems, for much of this time, system leaders, specifically the College of Alberta School Superintendents, (CASS), did not engage the discursive circle. This paper identifies a probable rationale for the historic lack of engagement in technology and education policy by CASS. Concluding discussion offers reasons for and early impacts of CASS’ first formal move into provincial technology policy discourse System Leadership for Learning Technology Success.